Small RNA sequencing reveals sex-related miRNAs in Collichthys lucidus - Song, Wei; Gan, Wu; Xie, Zhengli; Chen, Jia; Wang, Lumin (Frontiers in Genetics, 2022)
Collichthys lucidus (C. lucidus) is an economically important fish species, exhibiting sexual dimorphism in its growth rate. However, there are a lack of research on its underlying sex-related mechanisms. Therefore, small RNA sequencing was performed to better comprehend these sex-related molecular mechanisms. In total, 171 differentially expressed miRNAs (DE-miRNAs) were identified between the ovaries and testes. Functional enrichment analysis revealed that the target genes of DE-miRNAs were considerably enriched in the p53 signaling, PI3K–Akt signaling, and TGF-beta signaling pathways. In addition, sex-related miRNAs were identified, and the expression of miR-430c-3p and miR-430f-3p was specifically observed in the gonads compared with other organs and their expression was markedly upregulated in the testes relative to the ovaries. Bmp15 was a target of miR-430c-3p and was greatly expressed in the ovaries compared with the testes. Importantly, miR-430c-3p and bmp15 co-expressed in the ovaries and testes. This research provides the first detailed miRNA profiles for C. lucidus concerning sex, likely laying the basis for further studies on sex differentiation in C. lucidus.